Batch‐injection versus Flow‐injection Analysis Using Screen‐printed Electrodes: Determination of Ciprofloxacin in Pharmaceutical Formulations. Issue 2 (29th July 2015) - Stefano, Jéssica S.; Cordeiro, Denise S.; Marra, Mariana C.; Richter, Eduardo M.; Munoz, Rodrigo A. A.
Abstract: This article highlights the potential use of multi‐walled carbon‐nanotube modified screen‐printed electrodes (SPEs) for the amperometric sensing of ciprofloxacin and compares the association of batch‐injection analysis (BIA) and flow‐injection analysis (FIA) with amperometric detection. Both analytical systems provided precise (RSD<5 %) and sensitive determination of ciprofloxacin (LOD<0.1 μmol L −1 ) within wide linear range (up to 200 μmol L −1 ). Accuracy of both methods was attested by recovery values (93–107 %) and comparison with capillary electrophoresis. The BIA system is completely portable (especially due to association with SPEs) and provided faster analyses (130 h −1 ) and more sensitive detection than the FIA system due to the higher flow rates of injection. Abstract :